Efficacy of liposomal bupivacaine in pediatric patients undergoing spine surgery. Issue 11 (11th September 2018) - Cloyd, Colleen; Moffett, Brady S.; Bernhardt, Melanie Brooke; Monico, Evelyn M.; Patel, Nihar; Hanson, Darrell
Summary: Background: Liposomal bupivacaine may be an option for reducing opioid utilization in pediatric scoliosis surgery. The use of liposomal bupivacaine in this patient population has not been previously described. Methods: Patients who underwent posterior spinal fusion surgery at our institution from 2011‐2016 were identified. We performed a retrospective matched cohort study, matching patients who received intraoperative liposomal bupivacaine by age, gender, and extent of surgery to patients who did not. The primary endpoint was the use of morphine equivalents in the first 72 hours after surgery. Data collection included demographic and surgical data, pain medication utilization, and pain scores. Area under the curve (AUC) for pain scores was calculated. Descriptive statistical methods and univariable analysis were used to compare patients who received liposomal bupivacaine to patients who did not. Results: One hundred and forty‐one patients met study criteria; 47 patients who received liposomal bupivacaine were matched to 94 control patients who did not receive liposomal bupivacaine. No significant differences were noted in the patient population with the patients requiring a median of 11 segments (range 10‐13 segments) fused. Patients received a mean of 56.6 ± 37.4 mg/kg of intravenous acetaminophen, a mean of 3.4 ± 2.1 mg/kg of intravenous ketorolac, and 1.9 ± 0.93 mg/kg of morphine equivalents in the first 72 hours after surgery. On univariable analysis, no differences were noted in intravenous acetaminophen use, pain score AUC, intravenous ketorolac use, or morphine equivalents (2.0 ± 98 vs 1.8 ± 0.82) in patients who did not receive liposomal bupivacaine as compared to those patient who did received liposomal bupivacaine. Conclusion: Liposomal bupivacaine was not associated with reductions in postoperative opioid use in pediatric spinal surgery.